Risky behaviours and attitude of healthy Nigerians towards kidney failure: a case study of Ede North Local Government workers (2015)
Objective: This research work is aimed at determining the kidney failure risk behaviours and attitudes of healthy populace of workers of Ede North Local Government Area of Osun State, Nigeria. Methods: We adopted a descriptive survey research method. The study population consisted of both male and female local government workers in Ede North Local Government Area of Osun State. A self developed questionnaire, Kidney Failure Risk Behaviours (KFRB) research instrument, with nine items and two point response scale of' ,Yes' and 'No' was administered and completed questionnaire was collated, coded and analysed using descriptive statistic of frequent count and percentages to describe the demographic characteristics of the respondents. Bar and pie charts were used to analyze the data relating to risk behaviours and attitude of the respondents to kidney failure. Results: The study showed that the common kidney failure risk behaviors exhibited by workers in Ede North Local Government Area of Osun State are the use of herbal remedies 284 (85.8%), use of alcohol 239 (72.2%) and cigarette smoking 134 (40.1%). The study also showed that 183 (55.3%) were indifferent, 44 (13.3%) had positive attitude while 104 (31.4%) had negative attitude towards kidney failure. Thus majority of the respondents were indifferent towards kidney failure. Conclusion: The reflections of their attitude about their knowledge of kidney failure in their exhibitions of risk behaviours for kidney failure are strong indications of the need for health advocacy on kidney failure of these groups of workers and the healthy populace.